Life cycle assessment of a prefabricated house for seven locations in different climates. (1st August 2022) - Tavares, V.; Freire, F.
Abstract: Prefabricated buildings use lighter materials and have lower embodied impacts than conventional buildings. Previous studies assessed mainly energy and carbon, or a specific life cycle stage. However, increased operational energy can compromise the lower embodied impacts of lightweight prefabricated buildings, so a comprehensive life cycle assessment is required. This article assessed a lightweight prefabricated house for seven house locations (addressing transport, climate, and electricity mix), three insulation levels, and two heat pumps. A life cycle model was developed for a prefabricated one-bedroom house with a steel structure, addressing materials, transport to plant, modular prefabrication, transport to site, onsite assemblage, and use stage. A building information model (BIM) was integrated with the life cycle model to obtain the bill of materials, perform the energy simulation, and build the life cycle inventory. This comprehensive assessment includes abiotic resource depletion, abiotic depletion of fossil fuels, global warming, ozone layer depletion, photochemical oxidation, acidification, eutrophication, and non-renewable energy categories. Results show that embodied impacts for the Mediterranean and tropical climates are significant (up to 60%) for most impact categories. Prefabricated buildings should have different insulation levels: low level in a tropical climate, medium level in the Mediterranean, and high level in the EU continental region. Lightweight prefabricated buildings use fewer materials and can have lower embodied and operational impacts than heavyweight conventional, thus reducing the overall life cycle impacts of the building sector. Highlights: Lightweight prefabricated house assessed for 7 locations, 3 insulation levels, 2 heat pumps. BIM-LCA approach implemented to forecast energy needs and build the inventory. Lightweight prefabricated buildings can have lower embodied and operational impacts. Preferable insulation levels for continental, med. and tropical climates are identified. Impacts are more influenced by house location (electricity mix, climate) than insulation level.